1993
DOI: 10.2105/ajph.83.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the use of physical restraints in nursing homes: will it increase costs?

Abstract: OBJECTIVES. Reducing the widespread use of physical restraints in nursing homes is a primary goal of the federal nursing home reforms enacted as part of the Omnibus Budget Reconciliation Act of 1987. However, some nursing home operators assert that reducing restraint use could be prohibitively expensive, costing payors perhaps as much as $1 billion annually. We investigated whether nursing home residents free from physical restraint require more care and resources than similar residents who are restrained. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…Effect of nursing home wages on inappropriate antipsychotic use (1) (2) 286 D.C. Grabowski et al shown to require more staff time relative to a non-physically restrained resident (Phillips et al, 1993). The OLS results provide modest support for this hypothesis (see Table 4).…”
Section: Ols Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of nursing home wages on inappropriate antipsychotic use (1) (2) 286 D.C. Grabowski et al shown to require more staff time relative to a non-physically restrained resident (Phillips et al, 1993). The OLS results provide modest support for this hypothesis (see Table 4).…”
Section: Ols Resultsmentioning
confidence: 99%
“…Immobility resulting from the use of physical restraints has been found to increase the risk of pressure ulcers, depression, mental and physical deterioration and mortality (Zinn, 1993). Although greater staffing is typically correlated with a lower use of restraints, research has also suggested that -conditional on the level of staffing -residents who are physically restrained require more staff time than an otherwise similar non-physically restrained residents (Phillips et al, 1993). Federal law requires facility staff to remove physical restraints and reposition the nursing home resident every two hours; in addition, the regulatory requirements increasingly mandate that the staff document, in the facility's clinical records, the factors justifying use of physical restraints at any given time, generating further staff time burden.…”
mentioning
confidence: 99%
“…Rather, residents without restraints have been shown to require less care resources than residents in restraints, all other factors being equal [15]. Indeed, the negative consequences anticipated with restraint removal rarely occur.…”
Section: Discussionmentioning
confidence: 99%
“…Medicaid recipients provide a low level of funding to nursing homes (Kim, 1990). Although a recent study has shown that reductions in psychotropic drugs may be cost-effective (Phillips et al, 1993), the perception that reducing psychotropic drugs is expensive because it entails using more staff time may still persist in the nursing home industry. Therefore, facilities with a high Medicaid census may view themselves as more constrained with regard to costs because of the lower payments received.…”
mentioning
confidence: 99%